Partisipasi Masyarakat untuk Kesehatan Anak Berbasis Local Wisdom Melalui Rumah Gizi di Desa Kucur Kecamatan Dau Kabupaten Malang - Ika Anggraheni; Yorita Febry Lismanda (Jurnal Pemberdayaan Masyarakat, 2021)
Nutrition is an important factor for child development. Parents' knowledge about nutrition plays a role in determining children's nutrition. Parents must determine balanced nutrition for their children. The balance of carbohydrates, protein, vitamins, and other nutrients can increase the child's immunity to disease. The community service team tries to carry out a service program regarding the imbalance between the potential available in an area with the ideal conditions of the community. Local wisdom in the form of corn, cassava, and peanut farming in Kucur Village has not been followed by public awareness about the maximum utilization of local wisdom. The service is carried out with the aim of making guardians of kindergarten students in Kucur Village able to process food that is of interest to children. The target of this program is parents of kindergarten / RA children in Kucur village. The method of implementing the program begins with inculturation, discovery, design, define, monev and reporting of results. As a result of this dedication, the parents have knowledge of their local wisdom so that they can be used to support children's health through nutritious food. Parents have the initiative and are passionate about getting nutritious food for their children